Implementation of the Time Token Learning Model to Improve Students' Learning Outcomes in Islamic Cultural History Subject for Grade VI at MI Nurussalam Mantingan - Kamilatun Nisa, Fathimah; Roihatal Jannah, Adilla; Dina Savitri, Adella; Malicha, Ichda (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
The teaching of Islamic cultural history has often been teacher-centered, where the teacher transfers knowledge to passive students. This phenomenon is also observed at MI Nurussalam Mantingan, where many students struggle with solving problems, resulting in low learning outcomes. This is attributed to the lack of opportunities for students to think critically, express their ideas, and write proficiently. To address this issue, the researcher implemented a cooperative learning model to activate students and enhance the learning process, with one such model being the Time Token cooperative learning model. The research problem addressed in this study is whether the implementation of the Time Token cooperative learning model can improve students' learning outcomes. The aim of this research is to investigate students' learning outcomes after the implementation of the Time Token cooperative learning model. This study employed Classroom Action Research (CAR), with the subjects being 24 sixth-grade students at MI Nurussalam. Data were collected through observation sheets for teacher and student activities, as well as test items to measure students' learning outcomes using percentage formulas. The analysis of the data revealed that students' learning outcomes increased from 58% in Cycle I to 92% in Cycle II. It can be concluded that students' learning outcomes significantly improved through the implementation of the Time Token cooperative learning model, with a 92% increase in learning outcomes.